Usporedna analiza mrežnih izdanja Vjesnika bibliotekara Hrvatske i službenih glasila europskih knjižničarskih društava - Vrana, Radovan (Array, 2007)
Summary: The article presents the results of the research of Web versions of the journal Vjesnik bibliotekara Hrvatske and official publications of the European librarians' associations. The research included total of 43 official publications (bulletins and journals) from 35 European countries available on the World Wide Web. The publications were compared against a list of criteria divided in six major categories with high impact on the perception of the librarians' associations official publications on the World Wide Web. The results indicate differences in quality and quantity of content of the Web versions of the researched publications, quality of Web sites hosting these publications, and quantity and quality of basic information about the publications and novelty of information on the Web sites hosting the researched publications. The Web pages of Vjesnik bibliotekara Hrvatske are rich with information and the information are well organized. The conclusion of the research is that Web versions of the official publications of the European librarians' organizations in general should not be a pure copy of their printed versions but rather they should use all the advantages the World Wide Web can offer